Effect of pruning in Jatropha (Jatropha curcas Linn.) and fertility levels in wheat on performance of agrisilviculture system in Tarai Region of Uttarakhand - Yadav, R.P.; Bana, O.P.S.; Kaushal, R.; Rajput, P.R. (Indian Journal of Agroforestry, 2020)
The investigation was carried out at Agroforestry Research Centre, Haldi, G.B. Pant University of Agriculture and Technology, Pantnagar, to study the effect of four pruning height (no pruning, 50, 100 and 150 cm) in Jatropha and three fertility levels (50, 100 and 150% of recommended dose of NPK) in wheat on soil nutrients and performance of agrisilviculture system. The grain, straw and biological yield was significantly influenced by fertility levels, whereas, the effect of pruning height appeared to be non-significant. Grain, straw and biological yield reduced to 12.56 - 16.56%, under Jatropha in comparison to sole crop. The number of productive shoots (i.e. spikes)/m, spike length (cm), number of grains per spike, grain weight/spike, and thousand grain weight were significantly influenced by fertility levels while, the effect of pruning height found to be non-significant, except for spike length. The successive increase in fertility levels had significant influence on wheat yield and yield attributes. Number of spikes/m row and number of grains/spike appeared to be most important yield attributes. Both the pruning and fertility treatments significantly influenced growth and seed yield in Jatropha. The pruning in Jatropha had a positive effect on net change in soil fertility level.